2012
DOI: 10.1371/journal.pone.0035384
|View full text |Cite
|
Sign up to set email alerts
|

Conformational States of a Bacterial α2-Macroglobulin Resemble Those of Human Complement C3

Abstract: α2 macroglobulins (α2Ms) are broad-spectrum protease inhibitors that play essential roles in the innate immune system of eukaryotic species. These large, multi-domain proteins are characterized by a broad-spectrum bait region and an internal thioester, which, upon cleavage, becomes covalently associated to the target protease, allowing its entrapment by a large conformational modification. Notably, α2Ms are part of a larger protein superfamily that includes proteins of the complement system, such as C3, a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
(95 reference statements)
2
32
0
Order By: Relevance
“…4). These observations are thus supportive of fluorescence, analytical ultracentrifugation and native polyacrylamide gel electrophoresis (PAGE) studies of E. coli A2M that suggested that thioester cleavage did not lead to major conformational differences 32 , but differ from SAXS results obtained on the latter molecule, which indicated some degree of conformational modification on methylamine treatment 33 . Despite the fact that a major shift in domain positions could not be detected for Sa-A2M, reaction with methylamine caused cleavage of the thioester bond (Fig.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…4). These observations are thus supportive of fluorescence, analytical ultracentrifugation and native polyacrylamide gel electrophoresis (PAGE) studies of E. coli A2M that suggested that thioester cleavage did not lead to major conformational differences 32 , but differ from SAXS results obtained on the latter molecule, which indicated some degree of conformational modification on methylamine treatment 33 . Despite the fact that a major shift in domain positions could not be detected for Sa-A2M, reaction with methylamine caused cleavage of the thioester bond (Fig.…”
Section: Resultssupporting
confidence: 70%
“…1b). Previous studies with human and E. coli A2M have shown that reaction with methylamine inactivates the thioester and causes a major conformational change in the eukaryotic variant 5,19,32,33,[37][38][39] . To address the issue of a potential conformational change in a bacterial A2M on activation, we solved the crystal structure of methylamine-treated Sa-A2M.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like αMG, proteolytic cleavage of a bait region in bMGs results in a conformational change that allows the inhibitor to covalently capture the protease. The E. coli protein ECAM has a similar secondary structure to human plasma α 2 -MG and likewise contains an internal thioester to form covalent complexes with NE, trypsin and chymotrypsin [45]. …”
Section: Bacterial Mechanisms To Block Nspsmentioning
confidence: 99%
“…For successful encaging, at least two protomers are required to wrap around a standard-size endopeptidase (12), but the detailed molecular mechanism of tetrameric α 2 M inhibition is unknown, as only the molecular structure of induced hα 2 M is available (8). Little is also known about the physiology and function of bα 2 Ms, as only a YfaS-ortholog from Pseudomonas aeruginosa and ECAM have been partially studied to date (13)(14)(15)(16). The crystal structure of native α 2 M from Salmonella enterica (SEAM) is available (16), but its working mechanism is also unknown so far.…”
mentioning
confidence: 99%